(untitled) (Jurnal Bahasa, 2018)
This paper examines Malay Asli songs to determine the underlining phonological processes in singing. This is due to the fact that the elucidation of linguistic features in the Malay Asli songs remains scarce and unclear. For the purpose of this study, 10 Malay Asli songs were selected as the data, which were then phonetically transcribed from their MP3 format into text. The study places emphasis on the phonological processes concerning consonant segments. These were elaborated based on the theory of Generative Linear Phonology (Chomsky & Halle, 1968). The results indicated that a few of the underlining phonological processes in the singing of the Malay Asli songs are a reflection or manifestation of Standard Malay language. The singing corresponded to the phonological processes of Standard Malay language, which include glottalisation, nasal assimilation, voiceless obstruent deletion, nasal deletion, pharyngeal insertion and glide insertion. In addition, there was an absence of lateral trill deletion in the singing, as all of the singers retained the lateral trill /r/ in coda position. This shows that the singing of the Malay Asli songs violates the lateral trill deletion rule, which is an optional rule in Standard Malay language utterance. Keywords: Phonology, phonological process, Standard Malay, Malay Asli songs